2014
DOI: 10.1111/joac.12054
|View full text |Cite
|
Sign up to set email alerts
|

MGNREGA in Tamil Nadu: A Story of Success and Transformation?

Abstract: Social protection has emerged as a key driver of development policy at the beginning of the 21 st century. It is widely considered a 'good thing' that has the potential not only to alleviate poverty and vulnerability but also to generate more transformative outcomes in terms of empowerment and social justice. Based on an ethnographic study of the implementation of the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), India's flagship social protection policy, this article takes a critical look … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…(), found that the employment scheme fell short in terms of understanding life course issues for women, such as child rearing, and also failed to adequately consider the physical capabilities of women, particularly older women. In contrast, Carswell and De Neve () found that MGNREGA had positive effects on women as well as the poorest households in Tamil Nadu by providing them with a safety net.…”
Section: Background Literaturementioning
confidence: 92%
“…(), found that the employment scheme fell short in terms of understanding life course issues for women, such as child rearing, and also failed to adequately consider the physical capabilities of women, particularly older women. In contrast, Carswell and De Neve () found that MGNREGA had positive effects on women as well as the poorest households in Tamil Nadu by providing them with a safety net.…”
Section: Background Literaturementioning
confidence: 92%
“…The NREGA should not be judged in reference to an unattainable system without inefficiencies and politically motivated interventions, but as one that has exceeded the negative expectations of the prevailing consensus about the potential for rulesbased welfare and the practical realities of other welfare schemes. Carswell and De Nieve (2014) conducted a survey of MNREGA worksites in Tamil Nadu and found that the scheme benefited the poorest households, in particular Dalits, landless labourers and women. The NREGA had broader transformative effects in terms of raising agricultural wages across the sector, and raised the bargaining power of landless labourers by offering an alternative (often during the slow rainy season) source of income.…”
Section: Launch Of Various Mass Broad-based Rules-based Welfare Schemesmentioning
confidence: 99%
“…Later, seats in local government bodies, such as Panchayats, were also reserved for Dalits (Lerche, ). Government attempts to mitigate caste discrimination through legislation were complemented with social welfare policies from the 1960s onwards, including universal schooling, PDS (Public Distribution System), school midday meals, housing schemes and, more recently, the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) (Carswell and De Neve, , ; Heyer, ; Heyer and Jayal, ; Still, ). These policies not only aim to alleviate poverty but often target Dalits and tribal communities in particular, seeking to improve the material conditions of their livelihoods.…”
Section: Dalit Assertion In Indiamentioning
confidence: 99%
“…They don't have to work anymore because the government gives them everything: free TVs, free rice, free everything!’. Gounder landlords similarly complain that the availability of 100 days of paid work under MGNREGA, alongside the attractions of urban work, have not only pushed up agricultural wages, but also taken away much‐needed agricultural labour from the fields (Carswell and De Neve, , ). For Gounders, the PoA Act undermines their control over a rural agrarian and industrial workforce that until recently they were able to maintain through tightly managed relationships of socioeconomic domination and debt bondage.…”
Section: Gounder Perspectives On the Use Of The Poa Actmentioning
confidence: 99%